Oleothorax - P Gillardin; K J Mortelé; F Delens; A I De Backer (Journal of the Belgian Society of Radiology, 2013)
An 84-year-old woman presented with exertional dyspnoe, productive cough, but absence of chills, night sweats, or fever. Physical examination was unremarkable except for dullness and auscultatory absence of breath sounds over the right upper hemithorax. The patient’s previous medical history revealed the diagnosis of pulmonary tuberculosis at the age of 21. At that time, she was treated successfully with right artificial pneumothoraces and finally with “antiseptic oil”, but the patient was lost to follow-up thereafter.